ANALISIS KEPUASAN PENGGUNA TERHADAP KUALITAS WEBSITE SMK SMTI PADANG BERDASARKAN METODE WEBQUAL 4.0 - Febi Lailia; Dedy Irfan; Putra Jaya (Universitas Negeri Padang, 2018)
This study aims to determine the level of user satisfaction on the quality of SMK SMTI Padang’s website and to determine what factors that affect the level of user satisfaction through webqual 4.0 instrument consisting of usability variables, information qualilty, and service interaction. This reseacrh uses quantitative research method with multiple linear regression. The results of the analysis shows that the best quality of usability is the suitability with the type of website with the achievement of 43.71% while the worst is the attractive website appearance with the achievement of 20.87%, the best quality of information is the presentation of information with the appropriate format with a performance of 43.71%, while the worst is easy information to understand with the achievement of 20.13%, and the best quality of service interaction is personal information security with a performance of 42.71% while the worst is the reputation website 27,87%, and third variable webqual 4.0 usability, information quality, and service interaction have positive and significant effect to user satisfaction with correlation coefficient number 0,778. Keywords: user satisfaction, smtipdg.sch.id, webqual 4.0, multiple linear regression